The Role of Slow Speech Amplitude Envelope for Speech Processing and Reading Development - Ríos-López, Paula; Molnar, Monika T.; Lizarazu, Mikel; Lallier, Marie (Frontiers in Psychology, 2017)
This study examined the putative link between the entrainment to the slow rhythmic structure of speech, speech intelligibility and reading by means of a behavioural paradigm. Two groups of twenty children (Grade 2 and Grade 5) were asked to recall a pseudoword embedded in sentences presented either in quiet or noisy listening conditions. Half of the sentences were primed with their syllabic and prosodic amplitude envelope to determine whether a boost in auditory entrainment to these speech features enhanced pseudoword intelligibility. Priming improved pseudoword recall performance only for the older children both in a quiet and a noisy listening environment, and such benefit from the prime correlated with reading skills and pseudoword recall. Our results support the role of syllabic and prosodic tracking of speech in reading development.